2018
DOI: 10.5116/ijme.5ac6.44ba
|View full text |Cite
|
Sign up to set email alerts
|

Are alexithymia and empathy predicting factors of the resilience of medical residents in France?

Abstract: ObjectivesTo explore resilience, resilience predicting factors and resilience distribution in French medical residents. MethodsA cross-sectional study was conducted in which general practice residents (n = 380) were asked to answer the Jefferson Scale of Physician Empathy, the Connor-Davidson Resilience Scale, and the Toronto Alexithymia Scale. One hundred thirty-seven (137) responses were collected. The scores of the different scales have been calculated. The score differences were examined using the Student’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 61 publications
(56 reference statements)
6
48
0
Order By: Relevance
“…Given that past studies suggest that the association among gratitude, empathy and resilience is complex and ambiguous, the present study aims to unpack these relations. For example, research has shown that empathy is a significant predictor of resilience and may represent an emotional skill that is necessary to support resilience (Mathad, Pradhan, & Rajesh, 2017;Morice-Ramat, Goronflot, & Guihard, 2018). In contrast, some researchers have found no significant correlations between empathy and resilience (Olson, Kemper, & Mahan, 2015).…”
Section: The Present Study -Gratitude Empathy and Resiliencementioning
confidence: 99%
“…Given that past studies suggest that the association among gratitude, empathy and resilience is complex and ambiguous, the present study aims to unpack these relations. For example, research has shown that empathy is a significant predictor of resilience and may represent an emotional skill that is necessary to support resilience (Mathad, Pradhan, & Rajesh, 2017;Morice-Ramat, Goronflot, & Guihard, 2018). In contrast, some researchers have found no significant correlations between empathy and resilience (Olson, Kemper, & Mahan, 2015).…”
Section: The Present Study -Gratitude Empathy and Resiliencementioning
confidence: 99%
“…Individual adaptive or non-adaptive responses to adverse events depend on a variety of biological, cultural, social and psychological components, which can be encompassed in the concept of psychological resilience [ 43 ]. Past research found that resilience is directly related, on the one hand, to secure attachment [ 44 , 45 ], mental health [ 46 , 47 ], psychological well-being [ 48 ], empathy [ 49 ], mindfulness [ 50 ] and interoceptive awareness [ 51 ], and, on the other hand, inversely related to childhood trauma [ 45 ], anxiety, depression [ 52 ] and burnout [ 53 ]. Many studies have shown the link between measures of resilience and personality traits, such as harm avoidance, self-directedness, persistence and neuroticism [ 45 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Objective 1 : to establish whether the two groups of teachers, who had two opposite profiles of resilience at baseline (obtained from teachers’ personality profiles before the MOM course), were different at baseline in the other measures employed in our study as well. Based on previous research on resilience [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], we hypothesized that the low-resilience group, compared to the high-resilience group, had worse baseline levels of psychological well-being, mindfulness skills, interoceptive awareness, emotional distress, empathy and burnout (H1).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that a reduced resilience may be related to mood/anxiety, traumatic symptoms, neuroticism and alexithymia in Functional Neurological Disorders (Davydov, 2017;Jalilianhasanpour et al, 2018). Moreover, alexithymia was negatively correlated with resilience and empathy in a sample of French medical residents (Morice-Ramat, Goronflot, & Guihard, 2018).…”
mentioning
confidence: 99%